Pengaruh Temperatur Tempering Terhadap Pembentukan Struktur Mikro Dan Kekerasan Baja Skd 11 Untuk Tool Steel - Ihsan Saputra; Nugroho Pratomo Ariyanto; Mikie Febri (Politeknik Negeri Batam, 2020)
SKD 11 steel is a tool steel which is often applied in the manufacturing industry, such as cutting, punching, stamping tools, shear blades, dies and others. And in it’s application, of course steel must have a hard structure, strong and touhgness affected due to external forces causing deformation or change in shape. To improve the quality, heat treatment is required on the steel by providing austenizing, quenching and tempering temperature variations 400 °C, 550 °C and 650 °C. Which purpose to determine the hardness and microstructure of the tempering variation results. The first step of cutting material SKD 11 steel, followed by austenizing process up to 1050 °C and then quenching process (fast cooling) with medium water and continue the process of tempering variation 400 °C, 550 °C and 650 °C. After the heat treatment was complete, take hardness test and view the microstructure of the SKD 11 steel. At temperatures tempering 400 °C showed the highest hardness value of 56.5 HRC, followed by tempering temperatures 550 °C at 52.9 HRC and the lowest occurred at temperature tempering 650 °C at 39.1 HRC. Microstructure formed pearlite and martensite. Then the higher temperature tempering then the declining value of steel hardness SKD 11.